Status Concern and Relative Deprivation in China: Measures, Empirical Evidence, and Economic and Policy Implications - Xi Chen (Institute for the Study of Labor (IZA), 2015)
Status concern and the feelings of relative deprivation affect individual behavior and well-being. Traditional norms and the alarming inequality in China have made relative deprivation more and more intense for the Chinese population. This paper reviews empirical literature on China that attempts to test the relative deprivation hypothesis. We review the origins and pathways of relative deprivation, compare its economic measures in the literature, and summarize their applications. Drawing from solid empirical evidence, we discuss important policy implications on redistribution, official regulations and grassroots sanctions, and relative poverty alleviation.
Keywords: I14; I18; I32; B41; 330; inequality; status concern; relative deprivation; well-being; China